Human papillomavirus and survival of patients with sinonasal squamous cell carcinoma. Issue 7 (30th December 2019) - Oliver, Jamie R.; Lieberman, Seth M.; Tam, Moses M.; Liu, Cheng Z.; Li, Zujun; Hu, Kenneth S.; Morris, Luc G. T.; Givi, Babak
Abstract : Background: To the authors' knowledge, the question of whether human papillomavirus (HPV) infection is associated with outcomes in patients with sinonasal squamous cell carcinoma (SNSCC) is not well studied at this time. In the current study, the authors investigated patterns of HPV testing and its association with survival in patients with SNSCC using the National Cancer Data Base. Methods: The authors selected all SNSCC cases diagnosed between 2010 and 2016. HPV testing practices, clinicodemographic factors, treatments, and survival were analyzed. Multivariable Cox regression and propensity score–matched survival analyses were performed. Results: A total of 6458 SNSCC cases were identified. Of these, only 1523 cases (23.6%) were tested for HPV and included in the current study. The median patient age was 64 years and the majority had advanced stage tumors (overall AJCC stage III‐IV, 721 patients; 62.1%). HPV‐positive SNSCC comprised 31.5% (447 of 1418 cases) of the final study cohort. Among 15 hospitals that routinely tested nonoropharyngeal SCCs for HPV, the percentage of HPV‐positive SNSCCs was smaller (24.6%; P  = .04). Patients with HPV‐positive SNSCC were younger (aged 60 years vs 65 years; P  < .001), with tumors that were more likely to be high grade (55.3% vs 41.7%; P  < .001), and attributed to the nasal cavity (62.2% vs 44.0%; P  < .001). HPV‐positive SNSCC was associated with significantly improved overall survival in multivariable regression analysis (hazard ratio, 0.45; 95% CI, 0.28‐0.72 [ P  = .001]) and propensity score–matched (hazard ratio, 0.61; 95% CI, 0.38‐0.96 [ P  = .03]) analyses controlling for clinicodemographic and treatment factors. Conclusions: Currently, only a minority of patients with SNSCC are tested for HPV. However, a sizable percentage of SNSCC cases may be HPV related; furthermore, HPV‐positive SNSCC is associated with improved overall survival. Routine HPV testing may be warranted in patients with SNSCC. Abstract : A sizable percentage of sinonasal squamous cell carcinoma (SNSCC) cases may be related to human papillomavirus (HPV), and HPV‐positive SNSCC is associated with improved overall survival. Routine HPV testing may be warranted in patients with SNSCC.